I-Marks: An iris code embedding system for ownership identification of multimedia content. (October 2017) - Umar, Muhammad Muneer; Mehmood, Amjad; Song, Houbing; Choo, Kim-Kwang Raymond
Highlights: Human biometrics, like iris, are considered unique and cannot be changed unless damaged. Such biometrics can be used as a watermark to determine the exact ownership of a multimedia content. The proposed scheme converts the human iris data into iriscode and then embeds it into images for ownership identification purpose. Abstract: The owner of a work of multimedia content can be uniquely identified by embedding useful data into it. Here, we present a tool which can be used for embedding human biometrics data in multimedia content. Human biometrics are considered unique and cannot be changed unless damaged. Such biometrics can be used as a watermark to determine the exact ownership of a multimedia piece. We used the iris in the human eye for watermark creation. A usable code is generated from the iris known as iriscode. As this structure is specific to each individual, its use allows unique ownership identity of multimedia content. Graphical abstract: